MAGNETICALLY-FILTRATION PROPERTIES OF COMPOSITION GRANULAR NOZZLES OF MAGNETIC FILTERS - Гаращенко, В. І.; Астрелін, І. М.; Гаращенко, О. В. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2011)
Magnetically-filtration properties of composition granular nozzles of magnetic filters were investigated. It was shown that the size of middle induction in the volume of nozzle depends on correlation of the masses of granules of ferromagnetic and ferrimagnetic. The size of remaining magnetizing of composition nozzle in 2-3 times is less from the known ball-shaped nozzle. The influence of tensity of the external magnetic field on the size of coefficient of besieging was shown.